1999
DOI: 10.1016/s0959-3780(99)00020-5
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and future populations at risk of malaria

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
234
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(247 citation statements)
references
References 40 publications
3
234
0
1
Order By: Relevance
“…Several mechanisms have been hypothesized, including (i) increased travel from the malaria-endemic Lake Victoria basin to the highlands (20)(21)(22); (ii) degradation of the healthcare infrastructure (9-11); (iii) antimalarial drug resistance (22)(23)(24); (iv) local malaria transmission in the highlands as a consequence of land-use changes (9,11,25); and (v) global warming (8,26,27). Malakooti et al (10) analyzed the hospital clinical records and questionnaire survey results in a highland tea plantation estate in Kericho (Ϸ1,700 m above sea level), western Kenya, and concluded that the increased travel and healthcare infrastructure degradation should not be the key factors for the reemergence of highland malaria.…”
mentioning
confidence: 99%
“…Several mechanisms have been hypothesized, including (i) increased travel from the malaria-endemic Lake Victoria basin to the highlands (20)(21)(22); (ii) degradation of the healthcare infrastructure (9-11); (iii) antimalarial drug resistance (22)(23)(24); (iv) local malaria transmission in the highlands as a consequence of land-use changes (9,11,25); and (v) global warming (8,26,27). Malakooti et al (10) analyzed the hospital clinical records and questionnaire survey results in a highland tea plantation estate in Kericho (Ϸ1,700 m above sea level), western Kenya, and concluded that the increased travel and healthcare infrastructure degradation should not be the key factors for the reemergence of highland malaria.…”
mentioning
confidence: 99%
“…Several infectious agents are particularly sensitive to climatic conditions (McMichael et al, 2006). However, the socio-economic circumstances, such as economic well-being, can promote certain measures that inhibit the transmission of infectious disease (Martens et al, 1999). The spread of epidemics in human communities is co-determined by ecological and socio-economic aspects (Jones et al, 2008).…”
Section: Epidemics Climate Change and Economic Well-being In Ming Amentioning
confidence: 99%
“…It has been suggested-on the basis of the simple models mentioned earlier-that the incidence of malaria in the tropics could increase by up to 60% as a result of global warming (12,13,113). It has even been claimed that the recent recrudescence of the disease may be caused partly by warming that has already occurred (13,28,114).…”
Section: Malaria In the Tropicsmentioning
confidence: 99%